Stress influencing and coping strategies model among people living with HIV/AIDS: a mixed-methods - Handayani, Sri; Susanti, Dewi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Background: The influencing factor is stress, which has an impact on the low motivation of People Living With HIV/AIDS (PLWHA) to recover. By knowing these factors, interventions in controlling stress can be carried out well. A coping model is needed as a basis for developing stress control intervention plans for PLWHA using a family approach. As the closest environment to PLWHA, the family is very appropriate to control stress in PLWHA. Purpose: Â This research aims to determine the factors that influence stress and models of coping strategies for stress in PLWHA. Methods: This is a mixed-method study with an exploratory sequential approach. This research was conducted in Padang City at the quantitative research stage. The sample in this study was 38 PLWHA and nine respondents in a quantitative study (psychologists, counselors, HIV counselors, companions of PLWHA (husband/wife/children/parents), and PLWHA). Data collection was carried out through observation and deep interviews with the respondents. Results: The statistical analyses revealed that factors influencing stress are self-control and discrimination. The results of the interviews obtained information that PLWHA needs to increase their faith in God, PLWHA does not want their status to be known by many people, and there is a lack of knowledge of PLWHA and the environment regarding HIV/AIDS transmission. The appropriate coping strategy model for PLHIV is to increase the PLWHA’s faith, prevent the family from disclosing the PLWHA’s disease status to the environment, and increase the knowledge of PLWHA and the social environment. Conclusion: Self-control and discrimination influence stress. The stress control coping strategy model for PLWHA is formed from three pillars: faith/belief, health status, and knowledge.